Ocular torsion responses to electrical vestibular stimulation in vestibular schwannoma. Issue 11 (November 2018) - Mackenzie, Stuart W.; Irving, Richard; Monksfield, Peter; Kumar, Raghu; Dezso, Attila; Reynolds, Raymond F.
Highlights: Electrical vestibular stimulation (EVS)-evoked eye movements are trackable with an infrared camera. Unilateral vestibular schwannoma attenuated the ocular torsion response to EVS. EVS-evoked ocular torsion responses provide a convenient, non-invasive vestibular assessment. Abstract: Objectives: We determined if eye movements evoked by Electrical Vestibular Stimulation (EVS) can be used to detect vestibular dysfunction in patients with unilateral vestibular schwannoma (VS). Methods: Ocular torsion responses to monaural sinusoidal EVS currents (±2 mA, 2 Hz) were measured in 25 patients with tumours ranging in size from Koos grade 1–3. For comparative purposes we also measured postural sway response to EVS, and additionally assessed vestibular function with the lateral Head Impulse Test (HIT). Patient responses were compared to age-matched healthy control subjects. Results: Patients exhibited smaller ocular responses to ipsilesional versus contralesional EVS, and showed a larger asymmetry ratio (AR) than control subjects (19.4 vs. 3.3%, p  < 0.05). EVS-evoked sway responses were also smaller in ipsilesional ear, but exhibited slightly more variability than the eye movement response, along with marginally lower discriminatory power (patients vs. controls: AR = 16.6 vs 2.6%, p  < 0.05). The HIT test exhibited no significant difference between groups. Conclusions: These results demonstrate significant deficits in the ocular torsion response to EVS in VS patients. Significance: The fast, convenient and non-invasive nature of the test are well suited to clinical use.